Accusation: creating criminals - Pavlich, George C.; Unger, Matthew P. (Law and society series, 2016)
"The punitive effects of accusations that lead to criminalization have received considerable attention. Less well documented is the actual role, process, and meaning of accusation per se. This collection of essays sets out the terms of a new debate about a largely overlooked but foundational dimension of criminalizing justice; namely, accusation. As a figurative gatekeeper, accusation calls subjects to account, to avow truth about themselves in relation to historical orders through idioms recognizable and decipherable to criminal law's institutions. Criminal accusation, however, does more than define the outer borders of criminal justice institutions. It is directly implicated in providing a steady flow of potential criminals who are fed into expanding criminal justice arenas. Despite the basic politics through which legal persons are selected to face possible criminalization, there are few analyses directed at how accusation works in theoretical, historical, criminological, social, cultural, and procedural realms. The essays in this collection highlight the effects of accusatory moments where contextually imagined legal persons become potential subjects of criminalization. Incorporating interdisciplinary perspectives, rigorous scholarship, and a unique contribution to the field of socio-legal studies and criminology, this book establishes a new and important field of inquiry."--